Low-Level Laser Therapy to the Major Salivary Glands Increases Salivary Flow and MUC5B Protein Secretion in Diabetic Patients with Hyposalivation: A Preliminary Study - Wibawa, Awaludin; Sucharitakul, Jeerus; Dansirikul, Rungthip; Pisarnturakit, Pagaporn P; Bhuridej, Patita; Arirachakaran, Pratanporn (UI Scholars Hub, 2018)
Background: To investigate the effect of low-level laser therapy to salivary gland function in diabetic patients with hyposalivation. Methods: Twelve diabetic patients were recruited. A 940-nm indium-gallium-arsenide-phosphide low-power semiconductor diode laser was used to stimulate the major salivary glands with an irradiation time of 40 s; this was done three times a week for 2 consecutive weeks. Patients were given questionnaires related to dry mouth symptoms. Salivary flow rates, questionnaire responses as well as MUC7, MUC5B and histatin 5 protein salivary concentrations were assessed at the first and sixth visits after laser therapy as well at the 6-week follow-up visit. Results: The unstimulated salivary flow rate and MUC5B concentration at the follow-up visit significantly increased (p < 0.01). Histatin 5 concentration significantly decreased at the follow-up visit compared with that at the first visit (p < 0.05). The mean dry mouth score revealed a significant decrease in dry mouth symptoms at the sixth visit and follow-up visit compared with those at the first visit (p < 0.001). The positive correlation between dry mouth score and flow rate was the strongest at the sixth visit (rs = 0.549). Conclusions: Low-level laser therapy increased the salivary flow rate and decreased dry mouth symptoms in diabetic patients.